Effectiveness Of Implementing Electronic Traffic Law Enforcement (Etle) In Bogor City Law Area Satlantas Polresta Bogor City - Sundarta, Muhammad Diwan; Hartini, Sri; Hilman, Didi (JURNAL MAHASISWA YUSTISI, 2023)
This research is a study of the effectiveness of the implementation of Electronic Traffic Law Enforcement (ETLE) in Bogor City within the jurisdiction of the Bogor Municipal Police Traffic Unit. This study aims to find out how the implementation of Electronic Traffic Law Enforcement (ETLE) in Bogor City is a means of digitizing traffic violations or fines in the Bogor City community and to find out the efforts of the Bogor City Traffic Unit (Satlantas) in dealing with areas in Bogor City that do not yet have or have not reached Electronic Traffic Law Enforcement (ETLE). This research has descriptive analyst specifications using normative juridical methods based on data obtained through statutory law, scientific work, and field surveys, where the data that has been obtained is analyzed through the use of quantitative normative methods, which depart from positive legal provisions and arranged systematically without using mathematical models and systematic formulas. The result of this study is that the implementation of Electronic Traffic Law Enforcement (ETLE) in Bogor City has been carried out mobile and around, but not yet statically. Based on these results, the implementation of Electronic Traffic Law Enforcement (ETLE) in Bogor City has not been effective because the time and place of implementation are not fixed through mobile ETLE and mobile ETLE.